Topics in Modal Analysis II, Volume 8 Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014 - Allemang, Randall (Conference Proceedings of the Society for Experimental Mechanics Series,, 2014)
This critical collection examines a range of topics in modal analysis, from  finite element techniques to modal testing methods to shock and vibration, as presented in early findings and case studies from the Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014. The collection includes papers in the following general technical research areas:   ·         Finite Element Techniques ·         Modal Parameter Identification ·         Modal Testing Methods ·         Shock & Vibration.